Twitter, the End of Bipartisan Politics and the Rise of Populism. The Spanish Campaign in May 2015 - Gelado-Marcos, Roberto; Puebla-Martínez, Belén; Rubira-García, Rainer (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: The seemingly unshakable bipartisan political system in Spain started to crumble in the wake of the European Elections of 2014, giving way to a more fragmented distribution of seats. Such process crystallised in the Regional Elections of 2015, highlighting an already anticipated decay of traditional parties PP and PSOE and rise of populist parties like Podemos. Materials and Methods: Focusing on the discourse of Spanish politicians on Twitter, as one of the most recent political communication tools politicians had to learn to deal with, this paper offers a triangulation of quantitative and qualitative analysis. Results: We discuss, from a communication perspective, similarities and differences among parties and politicians on whether communication 2.0 changed and/or enriched political discourse leading up to a redistribution of parliamentary seats. Discussion: This paper stress the impact of social networks and the implementation of different communication strategies to address the collapse of bipartisanship in Spain. KEYWORDS: Twitter, bipartisanship, communication, campaign, Spain. Twitter, o fim da política bipartidária e a ascensão do populismo. A campanha eleitoral espanhola em maio de 2015 RESUMO Introdução: O sistema político bipartidário aparentemente inabalável na Espanha começou a desmoronar após as eleições europeias de 2014, dando lugar a uma distribuição mais fragmentada de assentos. Esse efeito se consolidou nas eleições regionais de 2015 com a derrocada dos partidos tradicionais, PP e PSOE, e a ascensão de partidos populistas como o Podemos. Materiais e Métodos: Ao focar no discurso dos políticos espanhóis no Twitter, como uma das mais recentes ferramentas de comunicação política com as quais os políticos tiveram que aprender a lidar, este artigo oferece uma análise que triangula técnicas quantitativas e qualitativas. Resultados: Discutimos semelhanças e diferenças entre os partidos e os políticos para verificar se a comunicação 2.0 mudou e/ou melhorou o discurso político e levou à redistribuição de cadeiras parlamentares. Discussão: O artigo fomenta o interesse de pesquisas sobre o impacto das redes sociais e da implementação de diferentes estratégias de comunicação política a fim de se entender o colapso do bipartidarismo na Espanha. PALAVRAS-CHAVE: Twitter, bipartidarismo, comunicação política, campanha eleitoral, Espanha.